2009
DOI: 10.1016/j.urology.2009.04.103
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac History and Risk of Post-cystectomy Cardiac Complications

Abstract: Objectives-Patients undergoing cystectomy often have significant baseline cardiac disease. Despite pre-operative medical optimization, post-operative cardiac complications remain a significant source of morbidity. We sought to evaluate risk factors for post-cystectomy cardiac complications (POCC).Methods-A retrospective review of all radical cystectomies for bladder cancer from 1/2004 through 9/2006 was performed. Twelve pre-operative risk factors were evaluated including age, Charleson Co-morbidity index, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…26 The Charlson score has been validated in a number of populations including general medical, 27 head and neck cancer patients, 28 prostate cancers patients 29,30 and elderly cancer patients. 31,32 Given previous reports that comorbidity is an important predictor of outcomes in various surgically managed cancers, [11][12][13][14][15] it is not surprising that the Charlson score was found to be a signifi cant predictor of complications after spinal metastasis surgery. In future spinal metastasis studies, it would be interesting to see how the Charlson score compares with other comorbidity assessment methods such as the Elixhauser Score.…”
Section: Recorded Datamentioning
confidence: 98%
See 2 more Smart Citations
“…26 The Charlson score has been validated in a number of populations including general medical, 27 head and neck cancer patients, 28 prostate cancers patients 29,30 and elderly cancer patients. 31,32 Given previous reports that comorbidity is an important predictor of outcomes in various surgically managed cancers, [11][12][13][14][15] it is not surprising that the Charlson score was found to be a signifi cant predictor of complications after spinal metastasis surgery. In future spinal metastasis studies, it would be interesting to see how the Charlson score compares with other comorbidity assessment methods such as the Elixhauser Score.…”
Section: Recorded Datamentioning
confidence: 98%
“…Age and comorbidity have been identifi ed as signifi cant predictors of complication after surgery for a number of cancer types. [11][12][13][14][15] Studies to date have not adequately investigated this issue for spinal metastasis. In one national database study, age (Continued) tember 2010 for the phrase "Charlson Score" or "Charlson Comorbidity Index" produced 729 matches covering topics as diverse as pulmonary lobectomy for lung cancer, 22 critically ill patients in tertiary ICU clinics 23 and restless leg syndrome in end-stage renal disease, 24 and various neurologic and spine surgery topics including long-term outcomes after laminectomy for lumbar stenosis 25 and predictors of mortality and complications in metastatic brain cancer patients.…”
Section: Recorded Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, patients with prior cardiac history who undergo radical cystectomy are more likely to develop complications. 4 Cystectomy as high risk, low-volume operation shows a volume-outcome relationship; less postoperative mortality and longer survival are reported for patients treated by high-volume providers. 5 The management of bladder cancer in this growing group of elderly is an increasing challenge.…”
mentioning
confidence: 99%
“…The presence of a comorbid condition may not only mask clinical signs of cancer and delay diagnosis, but may also preclude treatment options and even complicate the established cancer and/or effects of treatment (Piccirillo and Feinstein, 1996;Extermann, 2000;Prout et al, 2005;Hall, 2006). Several studies have found that bladder cancer is strongly associated with advanced age and tobacco smoking, each of which is associated with a distinct subset of additional comorbidities (Bjerregaard et al, 2006;Fisher et al, 2009). In addition, studies of European and North American populations have shown that the comorbid condition in bladder cancer is correlated to decreased overall survival after radical cystectomy (Megwalu et al, 2008;Fairey et al, 2009;Koppie et al, 2009;Lund et al, 2010).…”
Section: Commentmentioning
confidence: 99%